2008
DOI: 10.1021/ef800262s
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Water Content and Average Droplet Size in Water-in-Crude Oil Emulsions by Means of Near-Infrared Spectroscopy

Abstract: The main objective of this work is evaluating the influence of water content and average droplet size upon the near-infrared (NIR) spectra collected during water-in-crude oil emulsions synthesis and observing whether NIR spectroscopy may be used for predicting these properties simultaneously. It is shown that NIR spectra are sensitive to changes of the water content and average droplet size and that standard empirical models [partial least-squares (PLS)] may be built to correlate these properties and total abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…This will shift the spectra toward areas of higher absorbance for the emulsion with greater average droplet size. Araujo et al (2008) observed similar changes in the NIR spectra of water-in-crude oil emulsions due to changes in the average droplet size and concentration of water. However, the trends of the different spectra were opposite to those reported previously (Aske et al, 2002;Sjöblom et al, 2003).…”
Section: Introductionmentioning
confidence: 52%
“…This will shift the spectra toward areas of higher absorbance for the emulsion with greater average droplet size. Araujo et al (2008) observed similar changes in the NIR spectra of water-in-crude oil emulsions due to changes in the average droplet size and concentration of water. However, the trends of the different spectra were opposite to those reported previously (Aske et al, 2002;Sjöblom et al, 2003).…”
Section: Introductionmentioning
confidence: 52%
“…According to this theory, the intensity of a beam of light is exponentially attenuated while traversing a distance L through a particular medium. If multiple scattering is negligible, attenuation can be calculated by the following equation [75]:…”
Section: Near-infrared Spectroscopy (Nir)mentioning
confidence: 99%
“…Mathematical calculations have been performed by Rayleigh, Mie and Frauhhofer among others [76]. According to Rayleigh scattering, scatter intensity is a strong function of the droplets radius and the wavelength as described by the following equation [75]:…”
Section: Near-infrared Spectroscopy (Nir)mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, many efforts have been made to develop several typical instrumental techniques, such as capacitance method [3][4], microwave technique [5][6] and near-infrared spectroscopy [7][8]. The capacitance sensor depends on the significant difference in the dielectric permittivity of water and oil, changing the capacitance proportionally with the varying permittivity of the oil/water mixture.…”
Section: Introductionmentioning
confidence: 99%